Application of Several Concentrations of Palm Fiber Liquid Organic Fertilizer and the Composition of Planting Media on the Growth of Moringa Oleifera L - Mulyawati, Malika; Firnia, Dewi; Hilal, Samsu; Sodiq, Abdul Hasyim (Journal La Lifesci, 2025)
This study aims to analyze the effect of the application of several concentrations of liquid organic fertilizer based on palm fiber and the composition of plant media on the growth of moringa plants (Moringa oleifera L.). Palm fiber liquid organic fertilizer was chosen because of its potential as a source of environmentally friendly nutrients that can increase plant productivity. The study was conducted using a random group design (RAK) with treatment of various concentrations of liquid organic fertilizer (0%, 15%, 20%, and 25%) as well as variations of plant media by volume (1:1) (top soil, top soil + cocopeat, top soil + husk charcoal, and top soil + compost). The observed growth parameters included plant height, number of leaves, stem diameter, leaf chlorophyll, plant wet weight, leaf wet weight and root wet weight. The results showed that the concentration of liquid organic fertilizer of palm fiber and the composition of the plant media significantly affected the growth of moringa plants. The combination of 20% palm fiber liquid organic fertilizer concentration and top soil + compost (P2M3) provides the best growth results compared to other treatments. These findings provide important insights for the development of more efficient and sustainable moringa cultivation techniques.